The formation and development of health-saving competencies of university students - Sudakova, Yuliya E.; Feoktistova, Svetlana V.; Smirnova, Elena A.; Zhidikov, Vitaliy V.; Tkhugo, Muliat M.; Belyakova, Natalia V. (Opción, 2020)
The importance of the presented paper is determined by the fact that the worldview of Russian society is characterized by the emergence of awareness of the priority of the value of human health. It has been proved that the process of developing the health-saving competency of university students has positive dynamics provided that modern educational technologies are introduced into programs of study, namely, socio-psychological training which provides a concretization of the concept of “health-saving competency of a specialist”. It includes the implementation of a set of pedagogical conditions that ensure the effective formation of health-saving competency of students.